2023
DOI: 10.1007/s12063-023-00365-0
|View full text |Cite
|
Sign up to set email alerts
|

The application of complex network theory for resilience improvement of knowledge-intensive supply chains

Abstract: With frequent political conflicts and public health emergencies, global supply chains are constantly under risk interference, significantly reducing supply chain resilience (SCR), especially for the knowledge-intensive supply chains (KISCs). To assess and improve the resilience of KISC, this paper uses complex network theory to construct a directed weighted network model suitable for KISC and expresses the SCR as a comprehensive capability that can resist risk and recover from it. Using quantitative indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Security Magazine (2024) report indicates that software supply chain security is ranked as a key priority by 52% of chief information security officers and 70% of developers. However, the growing intricacy of contemporary software supply chains poses substantial hurdles in adequately monitoring and safeguarding each component and dependence (Chen and Wen, 2023). According to research by Chen and Wen (2023), unlike in the past when software was predominantly developed in-house by small teams, modern development practices now involve integrating opensource libraries with proprietary code across extensive development teams.…”
Section: Security Risks In Software Supply Chainsmentioning
confidence: 99%
“…Security Magazine (2024) report indicates that software supply chain security is ranked as a key priority by 52% of chief information security officers and 70% of developers. However, the growing intricacy of contemporary software supply chains poses substantial hurdles in adequately monitoring and safeguarding each component and dependence (Chen and Wen, 2023). According to research by Chen and Wen (2023), unlike in the past when software was predominantly developed in-house by small teams, modern development practices now involve integrating opensource libraries with proprietary code across extensive development teams.…”
Section: Security Risks In Software Supply Chainsmentioning
confidence: 99%
“…The review identifies the key methodological limitations in current models and proposes a conceptual framework that incorporates operational and topological aspects, alongside a new set of resilience metrics, to offer a more realistic representation of supply networks. Jiakuan Chen et al [28] studied the use of complex network theory to construct weighted network models suitable for knowledge-intensive industries to assess and improve industry resilience and development. Donghui Yang et al [29] conducted an in-depth study of the robustness structure of the supply chain and suggested focusing on establishing hub-like connections with upstream and downstream partners.…”
Section: Complex Network Theorymentioning
confidence: 99%
“…In the measurement of industrial chain resilience, researchers have employed a variety of indicators and methods to comprehensively capture its multidimensional nature. Core capabilities, performance metrics, and topological indices have been applied for evaluating industrial chain resilience across different levels [15][16][17][18]. Furthermore, mathematical models, simulation techniques, and statistical approaches have provided a diverse array of methodologies for studying this topic [19][20][21].…”
Section: Literature Reviewmentioning
confidence: 99%